Neural correlates of reward processing in schizophrenia: relationship to apathy and depression - Simon, Joe J.; Biller, Armin; Walther, Stephan; Roesch-Ely, Daniela; Stippich, Christoph; Weisbrod, Matthias; Kaiser, Stefan (Schizophrenia research, 2010)
The present study employs a new framework to categorise the heterogeneous findings on the relationship between impaired reward processing and negative and affective symptoms of schizophrenia. Based on previous behavioural and neuroimaging studies we postulate that “wanting” (i.e. anticipation) of a reward is specifically related to apathy, whereas “liking” (i.e. hedonic impact) is related to anhedonia and depression — symptoms commonly observed in schizophrenia. Fifteen patients with schizophrenia or schizoaffective disorder treated with atypical antipsychotic drugs and fifteen healthy controls performed a probabilistic monetary incentive delay task while undergoing functional magnetic resonance imaging. At the group level we found no significant differences between patients and controls in neural activation during anticipation or receipt of a reward. However, in patients with schizophrenia specific relationships between ventral-striatal activation and symptoms were observed. Ventral-striatal activation during reward anticipation was negatively correlated with apathy, while activation during receipt of reward was negatively correlated with severity of depressive symptoms. These results suggest that the link between negative symptoms and reward anticipation might specifically relate to apathy, i.e. a lack of motivation and drive. Impaired hedonic reward processing might contribute to the development of depressive symptoms in patients with schizophrenia, but it is not directly associated with self-rated anhedonia. These results indicate the necessity of more specifically differentiating negative and affective symptoms in schizophrenia in order to understand the role of the reward system in their pathogenesis.